Studies on Schismatoglottideae (Araceae) of Borneo XXXXIV: Piptospatha nivea, a new species from Kalimantan Tengah, Indonesian Borneo - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2014)
Piptospatha nivea is described and illustrated as new species, unique among Bornean Piptospatha by possessing a white spathe limb, and compared with the nearest most similar species, Piptospatha colata S.Y.Wong & P.C.Boyce. Aside from possessing a striking and unique inflorescence P. nivea represents an almost 300 km southerly extension to the known range of the genus.